Is There Any Correlation between Anti-Ro 52 Antibody Level with Hematological Abnormalities in Systemic Lupus Erythematosus? - Andiyang R. Diredja; Amaylia Oehadian; Laniyati Hamijoyo (Indonesian Journal of Rheumatology, 2022)
Background: Systemic lupus erythematosus (SLE) is a complex autoimmune disease with various clinical and serological manifestations. Previous studies have shown conflicting results about the association of anti-Ro 52 autoantibodies with hematological abnormalities in SLE. We investigated the correlation between anti Ro 52 autoantibody with anemia, leucopenia, and thrombocytopenia in patients with SLE. Methods: Sixty-two bio archives serum of an SLE patient at the Division of Rheumatology, Department of Internal Medicine, Hasan Sadikin General Hospital, Bandung, Indonesia from 2017 to 2019 were enrolled in the study. Anti-Ro 52 levels were examined using the ELISA method. The clinical data, treatment, and hematology paparametersere were analyzed retrospectively. Results: Among 62 bio-archive serum, four subjects were excluded because of incomplete data. Fifty-eight patients, all females were enrolled. We identified 57 (98.3%) subjects corticosteroid, 31 (53.4%) azathioprine and 28 (48.3%) chloroquine. A correlation coefficient of anti-Ro 52 levels and hemoglobin, leukocyte and platelets were -0.037 (p = 0.391), 0.065 (p = 0.315) and 0.092 (p = 0.246), respectively. Conclusion: No correlation was found between anti Ro 52 antibody levels with haematological abnormalities in patients with SLE. Further studies need to evaluate whether other antibodies play important role in haematological abnormalities in SLE.